Visceral Leishmaniasis, Northern Somalia, 2013–2019 - Aalto, Mikko K. (Emerg Infect Dis, 2020)
We identified visceral leishmaniasis caused by Leishmania donovani in a previously unknown focus in northern Somalia. Clinical and epidemiologic characteristics of 118 cases during 2013–2019 in Bosaso, the region’s commercial capital, have raised suspicion of visceral leishmaniasis endemicity status there.